Loss of HP1α alters nuclear integrity to promote cellular invasion : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University, Manawatū, New Zealand - Solomon, Raoul (Massey University, 2019)
The onset of invasion is a key step towards the development of metastatic cancer. For a cell to invade through interstitial spaces in the tissue requires a reduction in nuclear rigidity as the cell needs to deform to squeeze through small spaces. Heterochromatin Protein 1α (HP1α) is a protein that defines domains of heterochromatin, the highly compact regions of the genome, and is essential for maintaining the appropriate patterns of gene expression and genome stability. Loss or reduction of HP1α has been correlated with an increase in invasive potential in human tumours. Using an established model of Drosophila melanogaster epithelial cell invasion, the causative role HP1α plays in suppressing cellular invasive is confirmed within an epithelial tissue microenvironment. This model also demonstrates that loss of the Drosophila melanogaster HP1 homologue synergistically promotes cellular invasion in conjunction with an activated malignant signalling pathway. Importantly, human HP1α is shown to rescue this highly invasive Drosophila phenotype and demonstrates the relevance of this model to human disease, and its use for exploring protein interactions in a cellular microenvironment. As loss of nuclear integrity has been linked to a reduction in peripheral heterochromatin, the biophysical mechanisms by which HP1α acts as a suppressor of invasive potential were explored in the poorly invasive MCF7 breast cancer cell line with constitutive HP1α knock-down. These cells with reduced HP1α expression had a significant loss of nuclear membrane integrity and stiffness. The underlying nuclear lamina meshwork and associated peripheral heterochromatin was disrupted. This was associated with an increased solubility of lamina proteins, particularly lamin A, as well as the altered localisation of a number of peripheral nuclear proteins. In summary, this work established the important contribution of HP1α to the mechanical integrity of the nucleoskeleton and the role HP1α plays in suppressing malignant signalling pathways that promote cell invasion.
Keywords: Nucleolus; Nuclear proteins; Heterochromatin; Cell nuclei; Abnormalities; Cancer; Pathophysiology; 320506 Medical biochemistry - proteins and peptides (incl. medical proteomics)